Effect of thermal input, excess air coefficient and combustion mode on natural gas MILD combustion in industrial-scale furnace. (15th October 2021) - Huang, Mingming; Li, Ruichuan; Xu, Jikang; Cheng, Shen; Deng, Haoxin; Zhang, Bing; Rong, Zhiyu; Li, Yue
Highlights: The flow, flame and emission are presented under furnace operation condition. Smooth thermal field and reduced emissions were observed for MILD mode. Higer thermal input and excess air ratio anticipate the realization of MILD mode. From nonpremixed to premixed MILD mode, the NOx formation is suppressed. Heat balance under premixed MILD combustion was presented in the present work. Abstract: To promote the application of MILD scheme in furnace, the present work was performed to evaluate the effect of thermal input, excess air coefficient and combustion mode on the MILD combustion at high thermal level (thermal input varies from 600 to 786 kW); meanwhile, the heat from the utilized furnace was extracted by an annular water jacket and a corundum tube was installed in the furnace tube to create the high temperature atmosphere. The results were presented on flow field using numerical simulations and on global flame signatures, temperature/species distribution and exhaust emissions using experiments. Better combustion performance of MILD mode than conventional swirling diffusion combustion mode was verified in the present work. The positive effect of increased thermal input and excess air coefficient on gas recirculation, thermal uniformity and exhaust emissions reduction was observed. In the MILD combustion regime, the switching from nonpremixed to premixed combustion resulted in lower oxygen level and reduced reaction temperature in the combustion region, also much lower NOx emissions and slightly higher CO emission were observed. At 786 kW thermal input, the reaction zone covers the entire combustion chamber; meanwhile, low NOx emission level of 32 ppm@3%O2 are achieved for premixed MILD combustion mode. The MILD regime was established for natural gas fueled furnace with colorless distributed combustion and suppressed NOx and CO emissions.